(untitled) (Acta Entomologica Serbica, 2015)
A faunal study was carried out on plant bugs (Heteroptera: Miridae) from different sites and habitats in Sabzevar and its counties (Razavi Khorasan Province, IRAN) on various host plants. In total 20 species belonging to 16 genera were collected and identified from different host plants and localities.